Penerapan Teknologi Peningkatan Daya Tahan Buah Naga Menjadi Minuman Serbuk - Ramayani, Devi; Putra, Ikhsan Syafano; Raihan, Mohammad; Susanti, Riju; Rambe, Rodo Padena; Desmiarti, Reni; Sari, Ellyta (Politeknik ATI Padang, 2024)
Dragon fruit (Hylocereus spp.) is a tropical fruit that is rich in antioxidants such as vitamin C, polyphenols, flavonoids and betacyanins which have positive effects on human health. However, fresh dragon fruit has a short shelf life and can be damaged during storage and distribution. The aim of tecnology application is to increase the shelf life of dragon fruit by processing it into a powdered drink using the caramelization method. Caramelization is a heating technique that can improve the taste, stability and extend the shelf life of the product without reducing its nutritional value. In this project dragon fruit was heated until it caramelized, producing a more complex taste and aroma. After the caramelization process, the dragon fruit is dried and air-dried to produce powder. This process successfully improves the quality of the product, with a richer natural sweet taste. This project confirms that the caramelization method is effective in extending the shelf life of dragon fruit and maintaining its quality. The resulting dragon fruit powder drink provides an innovative solution in the storage and distribution of dragon fruit. This discovery opens up opportunities for the development of more efficient and healthier functional foods.